AB0141 Certolizumab pegol like reduces inflammation and bone damage in tmtnf transgenic mice. (12th June 2018) - Vieira-Sousa, E.; Caetano Silva, S.; Vidal, B.; Lopes, I.; Canhão, H.; Fonseca, J.E.
Abstract : Background: Transmembrane (tm)TNF (TgA86) mice is a transgenic line that spontaneously develops peripheral arthritis and spondylitis at 4 weeks of age, mimicking human spondyloarthritis (SpA). Objectives: The aim of this work is to understand the effect of TNF blockade in this SpA-like phenotype mouse strain, focusing on histological inflammation and bone damage. Methods: (tm)TNF (TgA86) mice were treated with a certolizumab pegol like product mice equivalent (Ab501), 100 mg/kg twice a week intraperitoneal, or with vehicle (phosphate buffer saline), for 12 weeks, in a therapeutic (10 weeks of age) and preventive (4 weeks of age) experimental settings. A semi-quantitative score for the severity of histologic inflammation and bone damage, in the paws (infiltration, lining cells, erosions and global), and in the spine (inflammation, intervertebral disc destruction, cartilage damage, bone erosion and ectopic chondrocytes/chondrophyte) was applied to haematoxylin and eosin stained slides. Results: 14 (tm)TNF (TgA86) mice (6M/8F) at 10 weeks of age (therapeutic group), and 15(tm)TNF (TgA86) mice (10M/5F) at 4 weeks of age (preventive group), were treated with Ab501; and 30 (tm)TNF (TgA86) mice with the respective vehicles, for a period of 12 weeks. A statistically significant reduction of the inflammatory infiltrate (p≤0.001), lining cells layers (p≤0.05), erosions (p≤0.05) and global inflammatory score (p≤0.05) of the paws, was observed in the Ab501 treated group, when compared to the vehicle group, both in the 10 and 4 weeks of age treatment groups. In the spine, statistically significant reductions of the inflammation (p≤0.001), intervertebral disc destruction (p≤0.05), cartilage damage (p≤0.001), bone erosion (p≤0.05), and ectopic chondrocytes/chondrophyte scores (p≤0.001) was also depicted in Ab501 treated group in comparison with vehicle. Conclusions: The certolizumab pegol like product mice equivalent reduced histologic inflammatory infiltrate in paws and spine of (tm)TNF (TgA86) mice. Bone damage, as defined by erosions in the paws and spine and ectopic chondrocytes/chondrophyte formation in the spine, also significantly improved in (tm)TNF (TgA86) mice. Acknowledgements: To Leonie M van Duivenvoorde and Dominique Baeten (Amsterdam Academic Medical Centre) for providing (tm)TNF (TgA86) mice for breeding and colony establishment. George Kollias from Flemming Institute for authorisation for the use this mice line. This investigator-initiated study was supported (financial and product) by UCB. Disclosure of Interest: None declared